2007
DOI: 10.1128/mcb.02141-06
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Activation of Poly(ADP-Ribose) Polymerase 1, Calpains, and Bax Is Essential in Apoptosis-Inducing Factor-Mediated Programmed Necrosis

Abstract: Alkylating DNA damage induces a necrotic type of programmed cell death through the poly(ADP-ribose) polymerases (PARP) and apoptosis-inducing factor (AIF). Following PARP activation, AIF is released from mitochondria and translocates to the nucleus, where it causes chromatin condensation and DNA fragmentation. By employing a large panel of gene knockout cells, we identified and describe here two essential molecular links between PARP and AIF: calpains and Bax. Alkylating DNA damage initiated a p53-independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

23
322
4
8

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 297 publications
(357 citation statements)
references
References 89 publications
(108 reference statements)
23
322
4
8
Order By: Relevance
“…In agreement with recent reports [19,20,32], PAR induces AIF release, which then translocates from mitochondria to the nucleus, leading to nuclear condensation and programmed cell death. Moreover, whether highdose-MNNG-mediated necrotic cell death is induced [20,32] or whether apoptotic cell death by low doses of the alkylating agent was analyzed, this did not change the death link between PARP-1 and mitochondrial AIF release. Thus, the PARP-1-generated death signal operates in both death pathways, although the pathways differ in substantial intermediary steps, such as the involvement of caspases.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…In agreement with recent reports [19,20,32], PAR induces AIF release, which then translocates from mitochondria to the nucleus, leading to nuclear condensation and programmed cell death. Moreover, whether highdose-MNNG-mediated necrotic cell death is induced [20,32] or whether apoptotic cell death by low doses of the alkylating agent was analyzed, this did not change the death link between PARP-1 and mitochondrial AIF release. Thus, the PARP-1-generated death signal operates in both death pathways, although the pathways differ in substantial intermediary steps, such as the involvement of caspases.…”
supporting
confidence: 78%
“…In contrast to recently published data showing that MNNG-mediated necrosis proceeds in a caspaseindependent manner [32], we observed that PAR polymer-induced cell death in HeLa cells after low doses of MNNG treatment could be prevented by caspase inhibition. In addition, we observed caspase cleavage of PARP-1 as well as caspases-7 and -9 activation, in combination with the results of the ADP/ATP-ratio assay, further corroborating an apoptotic form of cell death after low doses of MNNG.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Consistent with this phenotype, molecular analysis indicated that etoposide induced PAR ribosylation of proteins and the release of HMGB1 from the cells into the culture media (Figures 3b and c), two previously characterized hallmarks of programmed necrosis. 4,[18][19][20] In addition, the canonical apoptotic markers developed in response to the drug, including activation of the upstream initiator caspases2 and 9, and of the executioner caspases3 and 7 and the cleavage of their two substrates, PARP-1 and ICAD (Figure 3b and d). Also, fragmented nuclei and the release of cytochrome c from mitochondria to the cytosol were frequently detected (Supplementary Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…15 Next, the different components of this pathway (i.e., Atg5, DEDD, RHPN2) were knocked-down to assess their functional link to caspase3 activation. To this end, HeLa cells, which are rich in Cytokeratin, 18 were exposed to staurosporine, and caspase3 activation was quantified by the CaspaseGlo luminescent assay. We found that in this cellular setting the knock down of Atg5 reduced caspase3 activation, thus expanding the proapoptotic effects of Atg5 to other cell lines, and to another cell death-inducing agent (Figure 5d).…”
Section: Resultsmentioning
confidence: 99%